Retrieval of Long-Term Implanted Leadless Pacemakers: A Single-Center Experience - Minami, Kentaro; Neužil, Petr; Petrů, Jan; Chovanec, Milan; Hubbard, Chris; Hála, Pavel; Janotka, Marek; Škoda, Jan; Šedivá, Lucie; Reddy, Vivek Y (JACC. Clinical electrophysiology, 2020)
OBJECTIVES: The authors report their single-center experience with the retrieval and replacement of long-term implanted leadless cardiac pacemakers (LPs) and the factors contributing to success. BACKGROUND: LPs are a clinically effective and safe alternative to standard transvenous pacemakers for single-chamber ventricular pacing. However, the feasibility of retrieving and replacing long-term implanted LPs is not well known. METHODS: A total of 34 patients with implanted Nanostim LPs (mean implantation duration 1,570 ± 479 days) subsequently underwent retrieval. On the basis of fluoroscopic imaging, the cohort was divided into 2 groups: those with remarkable swinging movement (SM) of the LP docking button (n = 25) and those without SM (n = 9). RESULTS: The overall LP retrieval success rate was 85% (n = 29). New leadless devices were implanted in 27 patients immediately after LP retrieval. No procedure-related adverse events occurred. The rate of successful LP retrieval was significantly higher in the SM group (25 of 25 [100%]) than in the no-SM group (4 of 9 [44%]) (p < 0.001), and fluoroscopy time during the retrieval procedure was shorter in the SM group (12.7 ± 8.6 min) than in the no-SM group (45.6 ± 19 min) (p < 0.001). CONCLUSIONS: This study demonstrated the feasibility and safety of retrieval of long-term implanted LPs after a mean duration of 4 years. Retrieval was most successful in patients whose docking buttons exhibited significant SM.
Keywords: Pacemaker, Artificial; Equipment Design; leadless cardiac pacemaker; pacemaker retrieval; kardiostimulátor; Nanostim; lidé; protézy a implantáty; fluoroskopie; Fluoroscopy; design vybavení; Prostheses and Implants; Humans